STUDI PUSTAKA TENTANG PENYELENGGARAAN RUMAH SAKIT SYARIAH DAN PARIWISATA SYARIAH DI INDONESIA (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2022)
This research is a literature study that tries to explain how sharia hospitals and sharia tourism are organized in Indonesia. Phenomenological studies and descriptive analysis were used in this study. This research is a qualitative research with a literature review approach or library research. This research relies on secondary data collected from previous scientific journal publications as well as other reference sources relevant to the research topic. The results of the study indicate that there are several provisions for the operation of a sharia hospital according to the DSN-MUI Fatwa No. 107/DSN-MUI/X/2016. The fatwa includes indicators that must be used in the operation of hospitals based on sharia principles. The first is related to contracts, the second is about services, the third is about financial management, and the fourth is about medicines, food, beverages, cosmetics, and other materials which all must comply with sharia. As for sharia tourism, there is a DSN MUI Fatwa No. 108/DSN/MUI/X/2016 which regulates and determines the implementation of tourism based on sharia principles. This regulation covers everything related to sharia-based tourism business. Among them are both business managers and tourists must follow sharia principles; stay away from actions that are contrary to sharia principles; prevent disobedience, shirk, munkar, and other destructive activities; produce physical and spiritual benefits; and the fulfillment of material and spiritual needs in tourism.